Analisis Tingkat Kesehatan Bank Dengan Metode Risk Based Bank Rating (RBBR) Pada PT. BPR Supra Artapersada KC. Cibadak - Asep Sofwan Munandar; Mohamad Ramdan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The assessment rating of bank hlth is expected to evalute the prformance of the banking industry. Because bank healtiness represent good financial condition and good management. Risk-based Bank Rating (RBBR) method is used Bank Indonesia as a standard to appraise the rating of the bank health. This study to find out the sundeness level of bank in terms of the aspects of Risk profille, Good Corporate Govermance (GCG), Earnings, and Capital. This was an deskriptif analysis, with the object study is BPR Supra Artapersada Kc. Cibadak, PT. the data were collected through documentation and date analysis techniquen was an analysis of the soundness of bank using the Risk-Bases Bank Rating approach with an assesment converage including Non Ferforming loand, Loan to Deposit Rating, Good Corporate Governmence, Return on Assets, Operational costs on operating income, and Capital Adequacy Ratio factors. The resulth howed the condition of BPR Supra Artapersada Kc. Cibadak, PT. at “healthy criteria” with Non performing Loand of 1,8%, Loan to Deposit Rating of 85%, Maximum credit limit of 0,083%, Return on Assets of 0,034%, Operational costs on operating income of 0,070%, and Capital Adequacy Ratio of 41%..